MOAP‐1‐mediated dissociation of p62/SQSTM1 bodies releases Keap1 and suppresses Nrf2 signaling. (4th January 2021) - Tan, Chong Teik; Chang, Hao‐Chun; Zhou, Qiling; Yu, Chundong; Fu, Nai Yang; Sabapathy, Kanaga; Yu, Victor C
Abstract: Nrf2 signaling is vital for protecting cells against oxidative stress. However, its hyperactivation is frequently found in liver cancer through excessive build‐up of p62/SQSTM1 bodies that sequester Keap1, an adaptor of the E3‐ubiquitin ligase complex for Nrf2. Here, we report that the Bax‐binding protein MOAP‐1 regulates p62‐Keap1‐Nrf2 signaling through disruption of p62 bodies. Upon induction of cellular stresses that stimulate formation of p62 bodies, MOAP‐1 is recruited to p62 bodies and reduces their levels independent of the autophagy pathway. MOAP‐1 interacts with the PB1‐ZZ domains of p62 and interferes with its self‐oligomerization and liquid–liquid phase separation, thereby disassembling the p62 bodies. Loss of MOAP‐1 can lead to marked upregulation of p62 bodies, enhanced sequestration of Keap1 by p62 and hyperactivation of Nrf2 antioxidant target genes. MOAP‐1‐deficient mice exhibit an elevated tumor burden with excessive levels of p62 bodies and Nrf2 signaling in a diethylnitrosamine (DEN)‐induced hepatocarcinogenesis model. Together, our data define MOAP‐1 as a negative regulator of Nrf2 signaling via dissociation of p62 bodies. Synopsis: Stress‐induced p62/SQSTM1 bodies sequester the E3 ubiquitin ligase Keap1 from Nrf2, which is free to mediate transactivation of its target genes. MOAP‐1 recruitment to p62 bodies promotes their disassembly and reduces Nrf2 activation. MOAP‐1 interferes with liquid‐liquid phase separation of p62 bodies. MOAP‐1 disrupts p62 bodies by interfering with self‐oligomerization of p62 through binding to its PB1‐ZZ domains. Absence of MOAP‐1 leads to hyperactivation of Nrf2 signaling and increased tumorigenesis in a diethylnitrosamine (DEN)‐induced liver cancer mouse model. Abstract : Stress‐induced p62/SQSTM1 bodies sequester the E3 ubiquitin ligase Keap1 from Nrf2, which is free to mediate transactivation of its target genes. MOAP‐1 recruitment to p62 bodies promotes their disassembly and reduces Nrf2 activation.